Vanajyotsnā-sahastrasaumanasī = Vanajyotsnā-sahasrasaumanasī : Flora & plant kingdom in Sanskrit literature - Chatterjee, Jyotsnamoy, 1927-2001; Kulashreshtha, Abha, 1952-; Kulaśreshṭha, Jagadīśa Sahāya, 1922-; Kulaśreshṭha, Sushamā, 1945-; Anju Bālā (Kalidasa Academy of Sanskrit, Music & Fine Arts series ;, 2003)
Contributed articles on flora and fauna in Sanskrit literature; festschrift in honor of 75th birth anniversary of Jyotsnamoy Chatterjee, 1927-2001.